Collective and personal self‐esteem as mediators between perceived group discrimination and adjustment in Chinese migrant children. Issue 5 (10th February 2020) - Jia, Xuji; Li, Yaqian; Su, Peng; Liu, Xia; Lin, Danhua
Abstract: Previous studies have shown that perceived discrimination is negatively correlated with children's psychological development. However, how perceived group discrimination (PGD) leads to negative adjustment is not known. For 692 Chinese rural‐to‐urban migrant children, we examined the relations between PGD and both behavioral and emotional adaptation (antisocial behavior and positive affect), as mediated by collective self‐esteem (CSE) and personal self‐esteem (PSE). Children (50.7% boys; M age = 13.37 years) completed questionnaires on PGD, antisocial behavior, positive affect, CSE, and PSE. PGD was positively associated with antisocial behavior and negatively associated with positive affect according to structural equation modeling. CSE and PSE accounted for some of the PGD related to antisocial behavior and fully accounted for PGD effects on positive affect. These findings suggested that the combination of CSE and PSE is a potential mechanism that underlies PGD associated with both antisocial behavior and positive affect.